Kepatuhan Penderita Hipertensi yang Berobat Jalan dalam Menjalankan Diet Hypertensi di Rumah Sakit Jiwa Madani Palu - I Wayan Supetran (Biocelebes, 2008)
Commonly, hypertency can decided as permanent high blood pressure where systemic pressure is 140 mmHg and diastolic pressure over 90 mmHg. For the oldster population, hypertension was decided as systolic pressure over 160 mmHg and diastolic pressure over 90 mmHg. Recently, hypertension is one of the commonly death causation. Blood vessels complication is one from disease that caused by hypertension.This aim research is to observed the obedient of hypertension patient for running their diet program. Consecutive sampling was used for research method. Total respondence who participate in this research is 30 hipertension respondence The result showed that only 16 responden (53,3%) obedient to runnning their diet program. The other (46,7%) are not obedient. The age and the education level are influence for the respondence obedient to running their diet program. Key words: Hypertension, Diet Program.